Pemaknaan Teks Khutbah Idul Adha dalam Naskah Koleksi Pribadi Mgs. Muhammad Jufri: Kajian Filologi terhadap Nilai dan Pesan Dakwah - Ragil Pangestu; Irfan Swanto Yusni; Syafrizal Aziz; Hudaidah; Risa Marta Yati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The study of Islamic manuscripts contributes to understanding the development of thought, values, and social practices in Muslim communities, especially when texts are viewed as cultural artifacts. This research examines the Eid al-Adha sermon manuscript from the private collection of Mgs. Muhammad Jufri using a philological approach combined with value and da'wah analysis. The method is qualitative, applying philological stages such as inventory, description, transliteration, and textual criticism to produce a reliable text edition close to the original form. The analysis is strengthened by hermeneutics and da'wah studies to interpret meanings, values, and messages contextually. The findings show that the manuscript has a structured sermon format consisting of opening, main content, and closing, with strong rhetorical and religious functions. The text contains core values such as tawhid, obedience, sacrifice, social solidarity, and morality, as well as da'wah messages emphasizing piety, qurban practice, ukhuwah, and social awareness. Although limited by the absence of data regarding authorship and transcription time, the manuscript remains relevant as a source of Islamic values. This study shows that combining philology with interpretive approaches can enrich textual meaning and support Islamic studies development in contemporary society and strengthening cultural understanding among modern Muslim communities today worldwide context.